Fostering Independence for Correctional Assisted Residents as One of the Requirements for Getting Remission and Parole in Class I Prison Surabaya - Setiawan, Dio Wahyu; Rizky, Muchammad Catur; Hardyansah, Rommy (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Prisons are institutions or places that are responsible for coaching inmates. One of the coaching programs is in the form of fostering independence in the Surabaya Class I Correctional Institution. The program's objectives include allowing inmates to interact with fellow inmates during their sentences and preparing them for reintegration into society. However, this independence development program has experienced several obstacles due to the prison conditions exceeding capacity. The purpose of this research is to find out the prison's independence development program and how the process of fulfilling the rights of prisoners is. The research method with a problem approach is carried out using a normative juridical method with the source of the Law of the 1945 Constitution, Law Number 22 of 2022 concerning Corrections. The data analysis used is a qualitative data analysis technique. The results of the study show that the Class I Correctional Institution of Surabaya has implemented the inmate development program (especially the development of independence). In addition to increasing knowledge and expertise in the field of skills, participating in prisoner independence coaching is a requirement to be able to obtain prisoner rights. However, the coaching held is still constrained by the overcapacity of residents and the ability of trainers to provide coaching; besides that, qualified facilities and infrastructure are still not used effectively due to the limitations of the existing situation, conditions, and places. With the results of this research, it is hoped that it can add insight and can be used as evaluation material for Surabaya Class 1 Prison.